Thermodynamic control of patent tokenization for sustainable development - Peters, Andreas (Frontiers in Blockchain, 2025)
BackgroundPatent tokenization converts intellectual property (IP) into tradable digital units. Pilots on IPwe, IBM, and Ocean Protocol have processed >1,500 assets (≈$62 million since 2019). In practice, schedules are often fixed and pricing simplified; risk preferences are typically ignored—costing value in volatile settings relevant to the SDGs.MethodsWe cast patent tokenization as risk-sensitive control and linked economic risk aversion to inverse temperature. With the exponential transform Φ=e−γV, the risk-sensitive Hamilton–Jacobi–Bellman (HJB) linearizes for fixed controls; the optimal policy is a pointwise threshold (bang–bang or smoothly regularized). This preserves tractability and enables millisecond solves.ResultsFrom 45 tokenization trajectories (12 held out), we estimate γ=2.1±0.38 (95% CI), while a composite objective F(γ) calibrated to equity-like orders peaks at γ*≈3.02 ([2.9,3.2]). Monte Carlo (n=10,000) shows a ≈76% downside reduction and 92% success rate under ledger-based schedules. Solver latency drops by ∼850× (40 s → 47 ms).ConclusionThe thermodynamic lens explains why practice (γ≈2.1) deviates from the theoretical benchmark (γ*≈3.0) in our calibration: actors appear to trade maximal efficiency for robustness. The framework stabilizes revenues, drives fees to negligible levels, and supports SDG-aligned innovation finance by lowering the cost of access and adaptation under uncertainty.